Gambaran Asuhan Keperawatan pada Klien Anak yang Mengalami Peningkatan Suhu Tubuh dengan Dengue Hemorrhagic Fever di RS Meilia Cibubur - Diah Yuni Nusfantari; Restu Iriani (Jurnal Persada Husada Indonesia, 2021)
Dengue Hemorrhagic Fever is an infection caused by the dengue virus transmitted by the Aedes Aegepty mosquito characterized by sudden high fever, muscle, joint pain, loss of appetite, nausea, rash, and bleeding on the nose, mouth, gums, or bruises on the skin. Every year in Indonesia there are 17,877 cases with 115 deaths, most of them children. The research design of this scientific paper is qualitative descriptive research without direct intervention with the literary study approach. This research was conducted in a literature study by taking data from the 2019 research case due to the covid-19 pandemic period which is not possible to directly research in hospitals. The results of the study obtained data of clients experiencing sudden up-and-down fever with a temperature of 38.8°C, vomiting, coughing but rarely, tornikuet test (+), there are red spots with a number of spots >15 spots on the arm and a reddish rash on the feet. Based on the results of the study there was a major problem that was the increase in body temperature with the medical diagnose Dengue Hemorrhagic Fever. Interventions are carried out to address the problem of increased body temperature, one of which is a warm compress on the frontal and axial to lower the client's body temperature. In this study was not evaluated because there was no implementation directly to the client so that at the evaluation stage given an overview based on literature studies based on previous research journals where it showed there was a difference in body temperature in the child before and after given the action of compressing warm water with a value of p=0.000; α=0.05. Nurses to further enhance self-action based on evidance based to help lower the body temperature of clients with Dengue Hemorrhagic Fever.